DOI: 10.21007/etd.cghs.2006.0337
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Networks Modulating Retinal Injury

Abstract: Dissertation AbstractMany advances have and are being made with the advent of modern sciences. One area that remains resistant to significant advances is the recovery of the mammalian central nervous system (CNS) after injury. Considerable efforts were placed on understanding the cellular and biochemical changes occurring after injury and during wound healing. Aside from cataloging the changes that occur, little progress is being made in understanding the molecular cascades associated with the control of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 112 publications
(341 reference statements)
0
25
0
Order By: Relevance
“…We used quantitative trait locus (QTL) analysis to discover the mechanisms regulating gene expression (Vazquez-Chona et al 2005; Chesler et al 2005). Expression QTL (eQTL) analysis combines transcriptome profiling with linkage analysis to reveal chromosomal loci modulating expression variability (Darvasi, 2003; Broman, 2005; Chesler et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We used quantitative trait locus (QTL) analysis to discover the mechanisms regulating gene expression (Vazquez-Chona et al 2005; Chesler et al 2005). Expression QTL (eQTL) analysis combines transcriptome profiling with linkage analysis to reveal chromosomal loci modulating expression variability (Darvasi, 2003; Broman, 2005; Chesler et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Expression genetics has been instrumental in identifying candidate genes underlying complex traits, including disease and behavior (Aitman et al 1999; Karp et al 2000; Berge et al 2000). We previously found that a group of genes upregulated after central nervous system (CNS) injury (retina, brain, and spinal cord) also shares eQTLs in gene networks from the mouse forebrain (Vazquez-Chona et al 2005). Our analysis relied on the BXD recombinant inbred (RI) strains derived from experimental crosses between the C57BL/6 and DBA/2J strains (Taylor et al 1999; Peirce et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meta-analyses of brain expression data sets are also rare, thus far. Vazquez-Chona et al (2005) performed a metaanalysis of published expression data sets to identify a common response to neuronal injury. This is a good example of the use of disparate published data sets to draw biological inferences, in this case that some genes are commonly upregulated in the acute response to injury in retina, brain and spinal cord.…”
Section: Gene Expression Data Reuse In Neurosciencementioning
confidence: 99%